THE STRUCTURE OF NATIONAL PAYMENT SYSTEM AND PROSPECTS OF ITS DEVELOPMENT WITHIN THE FRAMES OF INTERNATIONAL PRINCIPLES OF ORGANIZATION - Irina V. Vashchekina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the key principles of payment system functioning according to international standards. The author advances an additional principle of the Russian payment system work in the changing political and economic conditions. Infrastructure of the national payment system subject to legal norms was shown. The article investigates institutional provision of the population with payment services: the structure of accounts opened by clients, which can be used for payments, including charge and credit cards; the number of accounts with distance access, opened in credit organizations. The author points out to different types of payment systems being developed in Russia today.